Characterization and drug sensitivity of a novel human ovarian clear cell carcinoma cell line genomically and phenotypically similar to the original tumor - Miriam Franklin; Lucy Gentles; Elizabeth Matheson; Nick Bown; Paul Cross; Angela Ralte; Connor Gilkes‐Immeson; Alice Bradbury; Maryam Zanjirband; John Lunec; Yvette Drew; Rachel O'Donnell; et al. (Cancer Medicine)
Abstract NUCOLL43 is a novel ovarian clear cell carcinoma (O‐CCC) cell line that arose from a primary culture of a patient's malignant ascites. The cells grow reliably in cell culture with a doubling time of approx. 45 hours and form colonies at high efficiency. They have a very high degree of loss of heterozygosity (LOH) affecting approximately 85% of the genome, mostly copy neutral and almost identical to the original tumor. The cells express epithelial (pan‐cytokeratin) and mesenchymal (vimentin) characteristics, CA125 and p16, like the original tumor. They also express ARID1A but not HNF‐1β and, like the original tumor, and are negative for p53 expression, with no evidence of p53 function. NUCOLL43 cells express all other DNA damage response proteins investigated and have functional homologous recombination DNA repair. They are insensitive to cisplatin, the PARP inhibitor rucaparib, and MDM2 inhibitors but are sensitive to camptothecin, paclitaxel, and NVP‐BEZ235. The NUCOLL43 cell line represents a distinct subtype of O‐CCC that is p53 and HNF‐1β null but expresses ARID1A. Its high degree of similarity with the original tumor genomically and proteomically, as well as the high level of LOH, make this an interesting cell line for O‐CCC research. It has been deposited with Ximbio.